Preparedness of Caregivers of Cancer Patients to Provide Care - KARABUĞA YAKAR, HATİCE; OĞUZ, SIDIKA (KARE PUBL, 2020)
OBJECTIVE This study aimed to investigate the preparedness of individuals providing care for cancer patients. METHODS This cross-sectional descriptive study was carried out with 203 Turkish cancer family caregivers in January-March 2019. The person who spent the longest time with the patient was chosen as the caregiver. The data were collected through face-to-face interviews with the Caregiver Introductory Form and Preparedness Scale of the Family Care Inventory. The scale consisted of eight items, the total score range is 0-32. Higher scores indicate that the caregiver feels more prepared for their role. Data were evaluated by independent groups t-test and one-way analysis of variance test. RESULTS The average age of caregivers was 46.86 +/- 13.8; most of them were female (64.5%). Caregivers' mean score of preparedness to provide care was 27.03 +/- 6.05. Caregivers' with moderate economic status were more ready to provide care than those with poor economic status (p<0.05). Caregivers who provided care for their patients for less than a year were more ready to provide care compared to those who cared for the patients for one to five years. Likewise, those who provided care for the patients for six to ten years were more ready to provide care than those who provided care for one to five years (p<0.05). CONCLUSION Caregivers with a modest economic status, those with less than one year of caregiving experience, and those with over five years of caregiving experience feel more ready to provide care.
Keywords: Cancer; care; caregiver; preparedness; FAMILY CAREGIVERS; BURDEN; CHALLENGES; EXPERIENCE; PROGRAM; MEMBERS